PERBANDINGAN SIFAT DAN KARAKTERISTIK BETON GEOPOLIMER TERHADAP BETON SEMEN PORTLAND UNTUK KEKUATAN STRUKTUR BALOK (COMPARISON OF THE PROPERTIES AND CHARACTERISTICS OF GEOPOLYMER CONCRETE AND PORTLAND CEMENT CONCRETE FOR STRUCTURAL BEAM STRENGTH) - N. Retno Setiati; Rulli Ranastra Irawan (Jurnal Jalan-Jembatan, 2018)
Fly ash is a coal combustion product from several power plants. Currently, F type fly ash is commonly used for concrete mixes. This study discusses the effect of 100% addition of fly ash on concrete mixes. In this study cement is substituted with fly ash. Laboratory testing is performed by making a physical model in the form of reinforced concrete beams. Test results were compared between geopolymer concrete and conventional concrete. To determine the mechanical properties of concrete, the specimen was made in a cylindrical shape measuring 150 mm x 300 mm and a beam measuring 150 mm x 150 mm x 600 mm. To determine the structural capacity of geopolymer and conventional concrete, two structural beams measuring 150 mm x 350 mm with a length of 4000 mm were made. The testing of structural beams was undertaken according to the ACI 437.1R-07. Then, the laboratory test results are compared to the theoretical analysis. Based on the results it was found that beams strength made of geopolymer concrete is almost equivalent to the conventional concrete. Based on the test results, the load capacity of the geopolymer concrete beam structure of 87.5 kN with a deviation of 38% for theoretical analysis. For conventional concrete, the load capacity is 109.2 kN with a deviation of 25% compared to theoretical analysis. In addition, the structural capacity value of geopolymer and conventional concrete beams based on the results of laboratory tests is smaller than the results of theoretical analysis. Keywords: Portland cement, fly ash, conventional concrete, geopolymer concrete, reinforced concrete beam